2022
DOI: 10.1039/d1ma01199e
|View full text |Cite
|
Sign up to set email alerts
|

MXenes: promising 2D materials for wound dressing applications – a perspective review

Abstract: Role of MXene in wound dressing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…MXene-based composites can be engineered to possess desired mechanical properties, such as flexibility and elasticity, effectively improving wound healing and providing necessary support for tissue regeneration. 80 One study found that MXene-based composites had a high mechanical strength and could maintain their mechanical properties even after immersing in simulated body fluids for up to seven days. 81 MXenes can be utilized as conductive elements in wound dressings, allowing for the delivery of electrical signals to the wound site.…”
Section: Advanced Wound Dressing/healing Applicationsmentioning
confidence: 99%
“…MXene-based composites can be engineered to possess desired mechanical properties, such as flexibility and elasticity, effectively improving wound healing and providing necessary support for tissue regeneration. 80 One study found that MXene-based composites had a high mechanical strength and could maintain their mechanical properties even after immersing in simulated body fluids for up to seven days. 81 MXenes can be utilized as conductive elements in wound dressings, allowing for the delivery of electrical signals to the wound site.…”
Section: Advanced Wound Dressing/healing Applicationsmentioning
confidence: 99%
“…The composite dressings are integrated with electrical signal measuring tools and bridged to smartphone for continuous monitoring of the healing progress 117 , 118 . MXenes are recent exploration in this direction of electroactive wound dressing, embedded in bacterial cellulose to promote cellular proliferation and migration at the wound site 119 , 120 . In a typical fabrication, as shown in Figure 4 B (a), the bacterial cellulose (BC) pellicles were resolved using NaOH and epichlorohydrin (ECH) cross linker to obtain regenerated bacterial cellulose (rBC).…”
Section: Nanotechnology and Theranosticsmentioning
confidence: 99%
“…Previous studies have demonstrated that incorporating 2D nanosheets into electrospun nanofibers enhances the mechanical properties of membranes and improves biocompatibility, which makes them suitable for wound dressing and scaffold applications [ 140 , 141 , 142 , 143 ]. Many researchers have investigated the significance of MXenes in wound dressing applications [ 144 , 145 ]. Among many elements, titanium carbide (Ti 2 C 2 Tx) has been used mainly for wound healing due to the antimicrobial and biocompatible nature of titanium [ 145 ].…”
Section: Biomedical Applications Of Electrospun Mxenes/polymeric Nano...mentioning
confidence: 99%
“…Many researchers have investigated the significance of MXenes in wound dressing applications [ 144 , 145 ]. Among many elements, titanium carbide (Ti 2 C 2 Tx) has been used mainly for wound healing due to the antimicrobial and biocompatible nature of titanium [ 145 ]. However, the direct use of MXene sheets in surgical incisions may create some problems.…”
Section: Biomedical Applications Of Electrospun Mxenes/polymeric Nano...mentioning
confidence: 99%